Comparing stimulus preference and response force in a conjugate preparation. Issue 1 (14th July 2021) - Davis, William T.; Rapp, John T.; Brogan, Kristen M.; Pinkston, Jonathan W.; Chinnappan, Barathi
Abstract : Researchers used a conjugate preparation to evaluate how response force changed based on participants' preferences for visual stimuli. First, researchers used a verbal preference assessment to evaluate each participant's preference for viewing for five object categories of visual stimuli; this process identified high preference (HP) stimuli and low preference stimuli for most participants. Thereafter, researchers exposed each participant to the five stimulus categories in a randomized order while using a force dynamometer to measure their response force to increase visual clarity of each stimulus. Results indicate the majority of participants' HP stimuli corresponded to the stimulus category for which they exerted the highest mean force. These preliminary findings suggest conjugate preparations involving response force may provide another option for measuring the relative value of some stimulus events.